Lack of bone healing: an unusual complication following surgically assisted rapid palatal expansion - Oliveira, T. F. M. de; Santos-Pinto, A.; Gabrielli, Mário Francisco Real [UNESP]; Pereira Filho, V. A. (Wiley, 2014)
Bone defects at interdental osteotomy sites are as a complication of surgi-cally assisted rapid palatal expansion (SARPE). The replacement of osseoustissue by fibrous connective tissue impairs the spontaneous closure of adiastema between central incisors, and orthodontic tooth movementthrough the defect area may lead to root resorption. Treatment of such asituation requires an orthodontic-surgical approach. In this report, wedescribe the lack of bone healing at the midline osteotomy site after SARPE,which was treated by autogenous bone grafting as assessed by cone beamcomputed tomography. In addition, we discuss factors related to the aetiol-ogy and treatment of a bone defect after SARPE.
Keywords: Maxillary expansion; maxillary transverse deficiency; Orthognathic surgery; Orthodontics